Effect of direct current pulses on mechanical and electrical properties of aged Cu–Cr–Zr alloys. (15th February 2016) - Wang, Wei; Li, Rengeng; Zou, Cunlei; Chen, Zongning; Wen, Wen; Wang, Tongmin; Yin, Guomao
Abstract: In this work, the response of Cu–Cr–Zr alloys to aging under direct current (DC) pulses was investigated. The results demonstrated that well-balanced mechanical properties and electrical conductivity can be achieved in case the alloys were properly treated. The aging behavior of Cu–Cr–Zr alloys is sensitive to DC pulses in the temperature range between 400 and 450 °C, whereas at temperatures out of this range, DC pulses have minor influences. The hardness of aged Cu–Cr–Zr alloy is increased by DC pulses while the electrical conductivity is slightly decreased. The peak hardness is increased by 10 HV after aging at 400 °C for 1 h. With the imposition of DC pulses, the precipitate size of Cr rich precipitates in aged Cu–Cr–Zr alloys is reduced from 238 nm to 178 nm, exhibiting stronger Orowan strengthening. After aging at 450 °C for 2 h with DC pulses, the Cu–Cr–Zr alloy has an average tensile strength of 609 MPa, elongation of 12.8%, and electrical conductivity of 77.6% IACS. A retarding effect of DC pulses on precipitation process is confirmed by synchrotron X-ray diffraction analysis, which is responsible for the slight decrease in electrical conductivity. Graphical abstract: Highlights: The imposition of direct current pulses refines the precipitates of Cu–Cr–Zr alloys. The refinement results in the superior mechanical properties. The mechanism of refinement is discussed in terms of precipitate growth through diffusion.